Verdicteye - Predict Court Judgements - Singh, Abhishek Kumar; Sharma, Aditi; Verma, Aishwarya; Srivastava, Ayush; Shukla, Pallavi (2025 3rd International Conference on Communication, Security, and Artificial Intelligence (ICCSAI), 2025)
India's legal system generates vast amounts of textual data, making it challenging to efficiently identify relevant Indian Penal Code (IPC) sections. Manual analysis is timeconsuming, labor-intensive, and prone to errors, necessitating an automated solution. VerdictEye utilizes NLP and machine learning to analyze incident descriptions and accurately predict relevant IPC sections. The system processes raw legal text using techniques like tokenization, stop-word removal, and TF-IDF vectorization to enhance structure and readability. Various machine learning models, including Logistic Regression, Random Forest, and Support Vector Machines (SVM), were trained for classification. Among them, Logistic Regression achieved the best accuracy and consistency, making it the preferred model for legal text classification. With a React-based interface, VerdictEye ensures real-time data input and predictions, enhancing accessibility for legal professionals. Future enhancements include incorporating ad- vanced NLP models, regional language support, and cloudbased deployment, positioning VerdictEye as a transformative tool for modernizing India's legal research process.